Türk medeni hukukunda çocuğun kişilik hakkının korunması - Haydaroğlu, Hale (My University, 2020)
Kişilik hakkına sahip olan çocuğun ihlallere karşı korunması gerekir. Çocuk ile ilgili her durumda çocuğun yararı dikkate alınmalıdır. “Türk Medeni Hukukunda Çocuğun Kişilik Hakkının Korunması” başlıklı bu tez çalışmamızda, çocuğun kişilik hakkının konusunu oluşturan kişisel değerleri, kişilik hakkının ihlali ve korunması incelenmiştir. Çocuğun kişilik hakkının hukuka aykırı fiil yolu ile ihlale karşı korunması kapsamında açılabilecek davalar, ayırt etme gücüne sahip olmayan çocuk ve ayırt etme gücüne sahip olan çocuk bakımından ele alınmıştır. Velayet ya da vesayet altında olan çocuğun kanuni temsilcisi dışındaki kişilere, kanuni temsilcisine ve kendisine karşı korunması incelenmiştir.

Children who have personal rights must be protected against infringements. The best interest of the child shall be taken into consideration in every situation related to the child. In this thesis titled “ Protection of Children’s Personal Rights in the Turkish Civil Law”, the personal values constituting the subject of the child’s personal rights, the violation and protection of the personal rights have been studied. Lawsuits which may be filed within the scope of protection against violation of the child’s personal rights through wrongful act are addressed in terms of the child with and without mental competence. The protection of the child under custody or guardianship against child’s own legal representative, child’s oneself and others has been studied.
Keywords: Children’s Personal Rights; Children’s Right to Action; Civil law; Custody; Çocuğun Dava Hakkı; Çocuğun Kişilik Hakkı; Çocuğun Yararı; Çocuk; Guardianship; Hukuk; Kişilik Hakkının Korunması Child; Law; Medeni hukuk; Protection of Personal Rights; The Best Interests of A Child; Velayet; Vesayet